Complex Bony Congenital Nasolacrimal Duct Obstruction Caused by an Adjacent Canine Tooth Bud. Issue 1 (January 2019) - Fayet, Bruno; Racy, Emmanuel; Bordonné, Corinne; Katowitz, William R.; Katowitz, James; Brémond-Gignac, Dominique
Abstract : The authors report the case of a 7-year old child with failed probing with stent intubation, who was found to have an unusual curvature of the nasolacrimal duct on the symptomatic side. CT imaging revealed a permanent maxillary canine tooth adjacent to the duct. It appeared that the relationship of the tooth bud to the curved nasolacrimal duct was most likely responsible for the symptoms of epiphora on this anomalous side. Abstract : A bony nasolacrimal duct can be associated with a permanent maxillary canine tooth bud.